2008
DOI: 10.1063/1.3056655
|View full text |Cite
|
Sign up to set email alerts
|

Early stage formation of graphene on the C face of 6H-SiC

Abstract: An investigation of the early stage formation of graphene on the C-face of 6H-silicon carbide (SiC) is presented. We show that the sublimation of few atomic layers of Si out of the SiC substrate is not homogeneous. In good agreement with the results of theoretical calculations it starts from defective sites, mainly dislocations that define nearly circular graphene layers, which have a pyramidal, volcano-like, shape with a center chimney where the original defect was located. At higher temperatures, complete co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
50
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 17 publications
(16 reference statements)
2
50
0
Order By: Relevance
“…Recently, it has been suggested that threading dislocations are efficient nucleation centers. 15 Using OM (Optical Microscopy) in the crossed polarization mode and in dark field mode, we evidence mainly two different growth features (see Figure 1a and 1b). the surface where they appear as yellow cones (see Figure 1c).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, it has been suggested that threading dislocations are efficient nucleation centers. 15 Using OM (Optical Microscopy) in the crossed polarization mode and in dark field mode, we evidence mainly two different growth features (see Figure 1a and 1b). the surface where they appear as yellow cones (see Figure 1c).…”
mentioning
confidence: 99%
“…We know already that such growth conditions allow the formation of FLG flakes over the whole SiC sample but not homogeneously. 7,15,16 This is because the process is not just intrinsic (simple sublimation of Si and reorganization of the C atoms to form graphene). In most cases, defects facilitate graphitization.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that defects in the SiC substrate serve as preferential centers for enhanced Si sublimation. 31 Thus, a higher growth rate of graphene could be expected around these defects, which may explain the formation of such graphite-like islands. The areas with homogeneous graphene layer thickness in Fig.…”
mentioning
confidence: 99%